Surgical wound dehiscence: A conceptual framework for patient assessment - Sandy-Hodgetts, Kylie; Carville, K.; Leslie, Gavin (Mark Allen Publishing Ltd., 2018)
© 2018 MA Healthcare ltd. This paper presents a conceptual framework which outlines the risk factors associated with surgical wound dehiscence (SWD) as identified in the literature. The purpose for the development of the conceptual framework was to derive an evidence-based, informed understanding of factors associated with SWD, in order to inform a programme of research on the aetiology and potential risk factors of SWD. Incorporated within the patient-centric conceptual framework are patient related comorbidities, intraoperative and postoperative risk factors related to SWD. These are categorised as either 'mechanical' or 'physiological mechanisms' posited to influence these relationships. The use of the conceptual model for assessment of patients has particular clinical relevance for identification of risk and the management of patients in the pre-, intra- and postoperative period.